(NmATEMATI^ESKIJ ANALIZ I GEOMETRIQ (B:s (NiZBRANNYE TRUDY SEMINARA n(B. (NbURBAKI (B: (NsBORNIK STATEJ (B: (NpER(B. (NS ANGL(B. (NI FRANC(B. /s - (NmANIN(B, (N`(B.(Ni(B.s; (NwAR^ENKO(B, (NaLEKSANDR nIKOLAEWI^s; (NnOWIKOW(B, (Ns(B.(Np(B.s ((NmOSKWA (B:s (NmIR(B,s, 1990)
(NbIBLIOGR(B. (NW KONCE DOKL(B.s
Keywords: (NgEOMETRIQs; (NmATEMATI^ESKIJ ANALIZs